Pokroky v revmatologii - Pavelka, Karel (Alter, 1996)
Kolektivní monografie.
Keywords: Infant; osteoporóza; Fatigue Syndrome, Chronic; Muscular Diseases; Anti-Inflammatory Agents; antifosfolipidový syndrom; Osteoporosis; syndrom chronické únavy; Rheumatic Diseases; Lyme Disease; antiflogistika; revmatologie; revmatické nemoci; dítě; Child; nemoci svalů; lymeská nemoc; Antiphospholipid Syndrome; kojenec